Rethinking the use of the term ‘Global South’ in academic publishing - Jaime Teixeira da Silva (European Science Editing)
‘Global South’, a term frequently used on websites and in papers related to academic and ‘predatory’ publishing, may represent a form of unscholarly discrimination. Arguments are put forward as to why the current use of this term is geographically meaningless, since it implies countries in the southern hemisphere, whereas many of the entities in publishing that are referred to as being part of the Global South are in fact either on the equator or in the northern hemisphere. Therefore, academics, in writing about academic publishing, should cease using this broad, culturally insensitive, and geographically inaccurate term.